Altered mitochondrial metabolism in the insulin‐resistant heart - Makrecka‐Kuka, Marina; Liepinsh, Edgars; Murray, Andrew J.; Lemieux, Hélène; Dambrova, Maija; Tepp, Kersti; Puurand, Marju; Käämbre, Tuuli; Han, Woo H.; Goede, Paul; O'Brien, Katie A.; Turan, Belma; et al. (Acta Physiologica, 2020)
Obesity‐induced insulin resistance and type 2 diabetes mellitus can ultimately result in various complications, including diabetic cardiomyopathy. In this case, cardiac dysfunction is characterized by metabolic disturbances such as impaired glucose oxidation and an increased reliance on fatty acid (FA) oxidation. Mitochondrial dysfunction has often been associated with the altered metabolic function in the diabetic heart, and may result from FA‐induced lipotoxicity and uncoupling of oxidative phosphorylation. In this review, we address the metabolic changes in the diabetic heart, focusing on the loss of metabolic flexibility and cardiac mitochondrial function. We consider the alterations observed in mitochondrial substrate utilization, bioenergetics and dynamics, and highlight new areas of research which may improve our understanding of the cause and effect of cardiac mitochondrial dysfunction in diabetes. Finally, we explore how lifestyle (nutrition and exercise) and pharmacological interventions can prevent and treat metabolic and mitochondrial dysfunction in diabetes.